2010
DOI: 10.1590/s1415-47572010005000083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of key gene encoding hypothetical DNA polymerase from B. mori parvo-like virus

Abstract: BmPLV-Z is the abbreviation for Bombyx mori parvo-like virus (China isolate). This is a novel virus with two single-stranded linear DNA molecules, viz., VD1 (6543 bp) and VD2 (6022 bp), which are encapsidated respectively into separate virions. Analysis of the deduced amino acid sequence of VD1-ORF4 indicated the existence of a putative DNA-polymerase with exonuclease activity, possibly involved in the replication of BmPLV-Z. In the present study, a recombinant baculovirus was constructed to express the full l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, both VD1 and VD2 genomes are characterized by having inverted terminal repeats (ITRs) at their ends that form a panhandle structure and share a common terminal sequence (CTS) of 53 nts [4]. VD1 contains four open reading frames (ORFs; ORF1 to ORF4), which encode nonstructural protein 2 (NS2) [5], nonstructural protein 1 (NS1) [6], a major structural protein (VP) [7,8], and DNA polymerase (PolB) [9], respectively. VD2 contains two ORFs, encoding a nonstructural protein 3 (NS3) [3] and a minor capsid structural protein (P133) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both VD1 and VD2 genomes are characterized by having inverted terminal repeats (ITRs) at their ends that form a panhandle structure and share a common terminal sequence (CTS) of 53 nts [4]. VD1 contains four open reading frames (ORFs; ORF1 to ORF4), which encode nonstructural protein 2 (NS2) [5], nonstructural protein 1 (NS1) [6], a major structural protein (VP) [7,8], and DNA polymerase (PolB) [9], respectively. VD2 contains two ORFs, encoding a nonstructural protein 3 (NS3) [3] and a minor capsid structural protein (P133) [10].…”
Section: Introductionmentioning
confidence: 99%
“…PolB is homologous to family B DNA polymerase, which is involved in protein-primed replication [15,16]. BmBDV is the only virus that possesses an ssDNA genome and encodes a DNA polymerase [9,17]. The function of NS3 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…VD1 and VD2 share a 53 nucleotide-long sequence at 3' and 5' termini, but the common terminal palindromic sequences which were widely existed in Parvoviridae could not be found in VD1 and VD2, implying that it is a new type of virus with unique replication mechanisms (Bando et al 1992(Bando et al , 1995. BmDNV-Z also owns the self-encoding DNA polymerase motif (Hayakawa et al 2000;Zhang et al 2010). In the 8 th Report of the International Committee on Taxonomy of Viruses, BmDNV-2 was excluded from the family Parvoviridae because of abovementioned reasons (Ito et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the ITRs form a “panhandle structure” [ 5 , 6 ]. A Basic Local Alignment Search Tool analysis revealed that VD1 contains a highly conserved domain of B family DNA polymerase [ 7 , 8 ]. In addition, BmBDV is the only virus that carries a single-stranded DNA that encodes a DNA polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…DQ017268 and DQ017269, respectively) [ 10 , 11 ]. Analyses of the BmBDV genome revealed that there are four open reading frames (ORFs) in VD1, which encode nonstructural protein 2 (NS2, VD1-ORF1) [ 12 ], nonstructural protein 1 (NS1, VD1-ORF2) [ 11 ], the major structural protein VP (VD1-ORF3) [ 13 ], and DNA polymerase (VD1-ORF4) [ 7 ], respectively. In contrast, VD2 contains two ORFs that encode nonstructural protein 3 (NS3, VD2-ORF1) [ 5 ] and the minor capsid structural protein (mCP) (VD2-ORF2) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%